Scoping review shows wide variation in the definitions of bronchopulmonary dysplasia in preterm infants and calls for a consensus. (8th December 2016) - Hines, Delaney; Modi, Neena; Lee, Shoo K.; Isayama, Tetsuya; Sjörs, Gunnar; Gagliardi, Luigi; Lehtonen, Liisa; Vento, Maximo; Kusuda, Satoshi; Bassler, Dirk; Mori, Rintaro; Reichman, Brian; et al.
Abstract: The use of different definitions for bronchopulmonary dysplasia (BPD) has been an ongoing challenge. We searched papers published in English from 2010 and 2015 reporting BPD as an outcome, together with studies that compared BPD definitions between 1978 and 2015. We found that the incidence of BPD ranged from 6% to 57%, depending on the definition chosen, and that studies that investigated correlations with long‐term pulmonary and/or neurosensory outcomes reported moderate‐to‐low predictive values regardless of the BPD criteria. Conclusion: A comprehensive and evidence‐based definition for BPD needs to be developed for benchmarking and prognostic use.